The Effect of Solution Focused Brief Therapy Group Counselling to Enhance the Self-Esteem of Primary School Students: / Keberkesanan Solution Focused Brief Therapy (SFBT) Melalui Perkhidmatan Kaunseling Kelompok dalam Meningkatkan Harga Diri Murid Sekolah Rendah (Sains Humanika, 2022)
This study was conducted to identify the effect of Solution Focused Brief Therapy (SFBT) group counselling to enhance the self-esteem of primary school students. The objective of this study was to find out the level of self-esteem and the difference in self-esteem score between the control and experimental group before and after the intervention. This study adopted the quasi-experimental research method. The Rosenberg Self Esteem instrument was used in this study to identify the level of self-esteem among primary school students before and after treatment. The study data were analyzed descriptively and inference using paired t-test. The group counselling sessions were observed and SFBT worksheets completed by the respondents were collected and analyzed qualitatively. Findings show that SFBT intervention had a positive effect on raising self-esteem among students in the experimental group from low to medium and high. The results of the study imply a significant difference in the level of self-esteem of students in the experimental group compared to the control group. In conclusion, efforts to identify students with low self-esteem and provide effective interventions such as SFBT at an early stage are very important to cultivate students’self esteem in order to achieve better mental health and wellbeing.
Keywords: Solution Focused Brief Therapy (SFBT), Group Counselling, Self-Esteem, Primary School Students